Toll-like receptor 8 ligands activate a vitamin D mediated autophagic response that inhibits human immunodeficiency virus type 1. - Grant R Campbell; Stephen A Spector (PLoS Pathogens)
Toll-like receptors (TLR) are important in recognizing microbial pathogens and triggering host innate immune responses, including autophagy, and in the mediation of immune activation during human immunodeficiency virus type-1 (HIV) infection. We report here that TLR8 activation in human macrophages induces the expression of the human cathelicidin microbial peptide (CAMP), the vitamin D receptor (VDR) and cytochrome P450, family 27, subfamily B, polypeptide 1 (CYP27B1), which 1α-hydroxylates the inactive form of vitamin D, 25-hydroxycholecalciferol, into its biologically active metabolite. Moreover, we demonstrate using RNA interference, chemical inhibitors and vitamin D deficient media that TLR8 agonists inhibit HIV through a vitamin D and CAMP dependent autophagic mechanism. These data support an important role for vitamin D in the control of HIV infection, and provide a biological explanation for the benefits of vitamin D. These findings also provide new insights into potential novel targets to prevent and treat HIV infection.